Vulnerabilities in health of garimpeiros of an Amazon region - Ferreira do Nascimento, Vagner (2019)
The objective of the study was to identify the health vulnerabilities of garimpeiros of an Amazon region. This is an exploratory and qualitative study, carried out in a garimpo in the Legal Amazon, in the interior of Rondônia, Brazil, in March 2017. Semi-structured interviews were conducted and the empirical data obtained were transcribed in full and submitted to content analysis. It was evidenced that the garimpeira activity amplifies the vulnerability situation of the worker, approaching him of situations of illness, especially for the non adoption of preventive measures. Despite the vulnerabilities that the activity implies, hazardous conditions and unhealthy work, the garimpeiros do not wish to leave the garment. The vulnerability of these garimpeiros is aggravated by their lack of knowledge about risk factors, such as direct and prolonged contact with water, sun exposure and the destruction of IPE, because they do not have health services in place and do not perform safe self-care practices. At the end of the study, it was noted that the existence of the current policies of the sector, do not guarantee living conditions, health and access to public services, which supports the vulnerability of these workers.